Biomedical Waste Management in India-A Review - Deepika Kanyal; Lata Kanyal Butola; Ranjit Ambad (Institute of Medico-legal Publications Pvt Ltd, 2021)
Biomedical waste is any kind of waste either solid or liquid containing infectious, potentially infectiousmaterials of medical, laboratory or research origin from activities such as diagnosis, prevention & treatmentof diseases. Bio-medical waste has a higher potential of infection and injury to the healthcare worker, patientand the surrounding community. It consists of human anatomical waste, animal waste, microbiology &biotechnology waste, waste sharps, discarded medicines & cytotoxic drugs, soiled waste, liquid waste,incineration ash & chemical wastes. Common generators of biomedical waste include hospitals, clinics,medical & veterinary colleges, blood banks, mortuaries, autopsy centers, biotechnology institutions, researchlaboratories, home health care & funeral homes. Hazardous chemicals & radioactive waste though noninfectious require proper disposal. World Health Organization states that 10% of hospital waste are infectious& 5% are non-infectious but hazardous waste. World Health Organisation has classified medical waste into8 categories which include general, pathological, radioactive, chemical, infectious, sharps, pharmaceuticals& pressurized wastes. In India, Biomedical waste (Management & Handling) Rules 1998 along with furtheramendments regulate biomedical waste management. It consists of 6 schedules which includes Categoryof Biomedical waste, Colour coding & type of container, Label for Biomedical waste containers or bagswhich should be non-washable & prominently visible, Label for transport of Biomedical waste containers orbags, Standard for treatment & disposal, Schedule for waste treatment facilities like Incinerator, Autoclave,Microwave System. Operating Standards like combustion efficiency & Emission Standards are defined.The present review article focused on basic issues as definition, categories, problems relating to biomedicalwaste and procedure of handling and disposal method of Biomedical Waste Management.